Article Correction: We Are on the Verge of Breakthrough Cures for Type 1 Diabetes, but Who Are the 2 Million Americans Who Have It? - Rebecca Smith; Samara Eisenberg; Aaron Turner-Phifer; Jacqueline LeGrand; Sarah Pincus; Yousra Omer; Fei Wang; Bruce Pyenson (Journal of Health Economics and Outcomes Research)
# Background